A comprehensive review of chronic heart failure pharmacotherapy treatment approaches in African Americans. (May 2019) - Tillman, Frank; Kim, Jennifer; Makhlouf, Tanya; Osae, Leah
Background: Our aim was to review the published literature evaluating treatment approaches for chronic heart failure (HF), notably as it relates to African American patients. Method: We undertook a comprehensive database search (1986–2017) of PubMed, EMBASE, and Ovid/MEDLINE utilizing terms 'African American', 'black', 'chronic heart failure', 'heart failure', 'medication', 'chronic therapy', and 'clinical trials'. Additional notable studies were obtained fromClinicalTrials.gov . Studies published in English that examine treatment modalities of chronic HF in African American and non-African American patients were included. Results: Examples of current gaps worthy of investigation include whether to maximize thiazides and calcium-channel blockers prior to adding renin–angiotensin system (RAS) inhibitors or beta blockers in HF with preserved ejection fraction; whether hydralazine/isosorbide dinitrate (ISDN) should be initiated during earlier HF stages; whether to prioritize hydralazine/ISDN over other agents such as RAS inhibitors; varying response of African Americans to different agents within drug classes; and the role of mineralocorticoid receptor antagonists. Conclusion: Further studies are needed in order for consensus guidelines to clarify how best to treat this population.